Respuesta :

Answer:

the question is incomplete, the complete question is "Finding second Derivatives In Exercise,find the second derivate.

[tex]f(x)=(3+2x)e^{-3x}[/tex]"

answer:[tex] \frac{df(x)^{2}}{dx^{2}}=(15+18x)e^{-3x}\\[/tex],

Step-by-step explanation:

To determine the second derivative, we differentiate twice.

for the first differentiation, we use the product rule approach. i.e

[tex]f(x)=u(x)v(x)\\\frac{df(x)}{dx}=u(x)\frac{dv(x)}{dx}+ v(x)\frac{du(x)}{dx}\\[/tex]

from [tex]f(x)=(3+2x)e^{-3x}[/tex] if w assign

u(x)=(3+2x)  and the derivative, [tex] \frac{du(x)}{dx}=2[/tex]

also [tex]v(x)=e^{-3x}[/tex] and the derivative  [tex] \frac{dv(x)}{dx}=-3e^{-3x}[/tex].

If we substitute values we arrive at

[tex]\frac{df(x)}{dx}=(3+2x)(-3e^{-3x})+2e^{-3x}\\\frac{df(x)}{dx}=(-9-6x)e^{-3x}+2e^{-3x}\\\frac{df(x)}{dx}=(-9-6x+2)e^{-3x}\\\frac{df(x)}{dx}=-(7+6x)e^{-3x}\\[/tex],

Now to determine the second derivative we use the product rule again

this time, u(x)=(7+6x)  and the derivative, [tex] \frac{du(x)}{dx}=6[/tex]

also [tex]v(x)=e^{-3x}[/tex] and the derivative  [tex] \frac{dv(x)}{dx}=-3e^{-3x}[/tex].

If we substitute values we arrive at

[tex]\frac{df(x)^{2}}{dx^{2}}=-((7+6x)(-3e^{-3x})+6e^{-3x})\\\frac{df(x)^{2}}{dx^{2}}=-((-21-18x)e^{-3x}+6e^{-3x})\\\frac{df(x)^{2}}{dx^{2}}=-((-21-18x+6)e^{-3x})\\\frac{df(x)^{2}}{dx^{2}}=(15+18x)e^{-3x}\\[/tex],